1-Pbps orbital angular momentum fibre-optic transmission - Liu, Junyi; Zhang, Jingxing; Liu, Jie; Lin, Zhenrui; Li, Zhenhua; Lin, Zhongzheng; Zhang, Junwei; Huang, Cong; Mo, Shuqi; Shen, Lei; Lin, Shuqing; Chen, Yujie; et al. (Light, science & applications, 2022)
Space-division multiplexing (SDM), as a main candidate for future ultra-high capacity fibre-optic communications, needs to address limitations to its scalability imposed by computation-intensive multi-input multi-output (MIMO) digital signal processing (DSP) required to eliminate the crosstalk caused by optical coupling between multiplexed spatial channels. By exploiting the unique propagation characteristics of orbital angular momentum (OAM) modes in ring core fibres (RCFs), a system that combines SDM and C + L band dense wavelength-division multiplexing (DWDM) in a 34 km 7-core RCF is demonstrated to transport a total of 24960 channels with a raw (net) capacity of 1.223 (1.02) Peta-bit s −1 (Pbps) and a spectral efficiency of 156.8 (130.7) bit s −1 Hz −1 . Remarkably for such a high channel count, the system only uses fixed-size 4 × 4 MIMO DSP modules with no more than 25 time-domain taps. Such ultra-low MIMO complexity is enabled by the simultaneous weak coupling among fibre cores and amongst non-degenerate OAM mode groups within each core that have a fixed number of 4 modes. These results take the capacity of OAM-based fibre-optic communications links over the 1 Pbps milestone for the first time. They also simultaneously represent the lowest MIMO complexity and the 2nd smallest fibre cladding diameter amongst reported few-mode multicore-fibre (FM-MCF) SDM systems of >1 Pbps capacity. We believe these results represent a major step forward in SDM transmission, as they manifest the significant potentials for further up-scaling the capacity per optical fibre whilst keeping MIMO processing to an ultra-low complexity level and in a modularly expandable fashion. A 1-Pbps orbital-angular-momentum fibre-optic transmission system that combines space-division multiplexing and wavelength-division multiplexing in a 34 km 7-core ring-core fibre is demonstrated utilizing low-complexity 4 × 4 MIMO equalization.